Stability of Velocity in the Group of Seven Countries : A Kalman Filter Approach - Bomhoff, Eduard (IMF Working Papers; Working Paper ;, 1990)
This paper estimates forecasting models using annual data for the income velocity of money in the G-7 countries. The predictions are conditional upon the realized value of the long-term domestic government bond rate. Such conditional forecasts did not deteriorate over the period 1980-1988 as compared with the earlier postwar period. Velocity of M1 is found to be very interest-elastic in almost all countries; velocity of M2 less so. The specifications (based on Kalman filters and smoothers) point to a non-constant (stochastic) trend in velocity, hence questioning the assumptions required for the cointegration techniques used in other research on the demand for money.